Presepsi Publik Terhadap Integritas Hakim: Analisis Survei Integritas Hakim oleh Komisi Yudisial RI - Utami, Nur Ahdiati Budi (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2025)
Integrity is a major aspect that greatly influences the credibility of a profession, including judges. Maintaining the integrity of judges is the responsibility of the supervisory institution for judges which is carried out internally by the Supreme Court and externally by the Judicial Commission. If the integrity of Indonesian judges is good, then the public perception will certainly be good, and vice versa. This study aims to prove the correlation between the integrity of judges and public perception and to analyze the role of the Judicial Commission in improving the Integrity of Judges. The research method used is quantitative descriptive research, which focuses on the problems of current phenomena related to public perception of the integrity of judges, and presents research results in the form of meaningful numbers based on KY performance data and survey results. The results of the study show that the role of the Judicial Commission (KY) in improving the integrity of judges is not optimal, as evidenced by the results of a survey conducted by the KY itself on its performance showing that public perception of the integrity of judges has continued to decline from 2022 to 2024. The study recommends a policy correction in an effort to maintain the integrity of judges which has an impact on decreasing public trust in the integrity of judges. First, the Policy for Strengthening Preventive Functions/Integrated Prevention Programs. Second, the pilot mechanism policy in certain areas - certain targets - certain focuses - certain time periods.